Manganate multiferroic materials : study of the effect of doping Sr in BiMnO3 bulk sample - Tan, Idy Hao Ning. (2009)
In the research field of multiferroic materials, progress has been made in synthesizing and characterizing Bismuth-based oxides in bulk form that possess multiferroism property to cater to the needs of the industry. Single phase BiMnO3 is difficult to prepare as the synthesis requires high temperatures and pressures. Doping to Bi(1-x)Sr(x)MnO3 is thus proposed to achieve BiMnO3 phase and to enhance the magnetic properties of BiMnO3. Hence there is a need to study the effects of doping Strontium (Sr) at the A-site of multiferroic BiMnO3. The objective of this report was to study the effects of BiMnO3 with different amounts of Sr doped in and the sintering temperature needed to obtain Sr-doped BiMnO3 phase. Crystallographic structure of the material was obtained using X-Ray Diffraction technique and the magnetic properties of the samples were tested using Vibrating Sample Magnetometer (VSM). It was found with dopant concentration of x=0.4, the temperature needed to obtain Sr-doped BiMnO3 phase is 900C but with x=0.6, the sintering temperature needed to obtain Sr-doped BiMnO3 phase is 800C. Higher magnetization is achieved for doped samples compared to undoped samples. Sintering temperature also played a part in affecting the magnetic property of the sample.